Selected Edith Wharton - Wharton, Edith (Saga Egmont, 2024)
Deep dive into American literature’s famous female writer with this remarkable collection of ‘Selected Edith Wharton’. Detailing the lives, loves and losses of a country’s people, we’ll start our journey with the isolated farmer and his mean and merciful wife in ‘Ethan Frome’. Next, we’ll explore a women’s pride and position in early 20th-century society in ‘Summer’. We’ll then head to the big smoke as Undine Spragg urges her parents to take action in ‘The Custom of the Country’. In ‘The House of Mirth’, we challenge a woman’s chances and choices. Whilst ‘Glimpses of the Moon’ sees a wealthy couple’s expectations shattered, we’ll explore the highs and lows of high society in ‘The Age of Innocence.’ Weaving together a thrilling collection of social status, chances, and choices for American society, ‘Selected Edith Wharton’ is the perfect companion for fans of ‘The Great Gatsby’, starring Leonardo Dicaprio. Edith Wharton (1862-1937) was an American novelist, short story writer, and the first woman to win the Pulitzer Prize for Literature. Her work spans ‘The Age of Innocence’, ‘The House of Mirth’, and ‘Ethan Frome’ – all of which were widely adapted for the screen in the 20th century. Inducted into the National Women’s Hall of Fame in 1996, Wharton remains today a huge influence on American English literature and culture.